THE EFFECT OF TEACHING LISTENING USING FOLKTALES ON STUDENTS’ LISTENING ACHIEVEMENT (A Case of Regular Class of Eleventh Grade at MAN 1 Kendari) - Mulya, Rahmita Arga; Nurnia, Nurnia; Siam, Siam (Journal of Teaching of English, 2019)
This study investigated the effect of using folktales on students’ listening achievement at the eleventh grade of MAN 1 Kendari. This study applied a Pre-experimental research design with one group pretest and posttest. The population   of   this   research   was   the   eleventh-   grade students of senior high school in the academic year 2018/2019. The sample of this research was all eleventh-grade students of MAN I Kendari which consists of 30 students. The  Technique  of sampling  used  by  the  researcher  was total sampling. The result showed there was a significant effect of using folktales on students’ listening achievement. It  was  proven  based  on  descriptive  analysis,  the  mean score of pretest was 48.4 and the posttest means score was 75.2.  Moreover,  the  result  of  hypothesis  testing  showed that the mean value of pretest and posttest was 26.7 and the standard deviation was 20.7, while the standard error means was 3.78. The sig. (2-tailed) was 0.000 which smaller than (<0.05), it can be concluded that H0 was rejected and H1 was accepted which means there was an effect of using Folktales in teaching Listening at Eleventh grade of MAN 1 Kendari. Keywords: listening, folktales